1988
DOI: 10.1002/pd.1970080507
|View full text |Cite
|
Sign up to set email alerts
|

In vitro characteristics of human fetal cells obtained from chorionic villus sampling and amniocentesis

Abstract: In vitro characteristics of human fetal cells have been investigated after chorionic villus sampling at the first trimester and amniocentesis at the second trimester of pregnancy. Light microscopy revealed heterogeneous morphology of cell types in both the chorionic villus culture and the amniotic fluid cultures. Based on the experiments performed, chorionic villus cells are more sensitive to pronase, trypsin, and versene during subculture and have a higher DNA content per single cell and release more [125I]-B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Secondary cultures. Because of the large numbers of cells needed for the experiments, primary cultures, established from 20-30 AF samples at 15-20 weeks' gestation, were subcultured by trypsin-EDTA (GIBCO,, and combined to grow in MEM-alpha medium supplemented with 20 per cent FBS, penicillin G (50 units/ml), streptomycin (50 pg/ml), fungizone (0.12 pg/ml), and glutamine (2 mM) in a 5 per cent CO, incubator at 37°C (Chang and Jones, 1985;1988). The same amount of single cell suspension (1 ml per plate) prepared from these subcultures was then seeded onto uncoated or coated (either by A F or by FBS) plates.…”
Section: Amniotic Fluid Cell Culturementioning
confidence: 99%
“…Secondary cultures. Because of the large numbers of cells needed for the experiments, primary cultures, established from 20-30 AF samples at 15-20 weeks' gestation, were subcultured by trypsin-EDTA (GIBCO,, and combined to grow in MEM-alpha medium supplemented with 20 per cent FBS, penicillin G (50 units/ml), streptomycin (50 pg/ml), fungizone (0.12 pg/ml), and glutamine (2 mM) in a 5 per cent CO, incubator at 37°C (Chang and Jones, 1985;1988). The same amount of single cell suspension (1 ml per plate) prepared from these subcultures was then seeded onto uncoated or coated (either by A F or by FBS) plates.…”
Section: Amniotic Fluid Cell Culturementioning
confidence: 99%
“…Redman et al (1984) showed a difference in Class I expression between extra-villous and villous trophoblast, the former being positive and the latter negative. These various data may be resolved by more refined methods to define, separate, and culture the cell types in chorionic villi (Niazi et al, 1981;Loke et al, 1986;Chang and Jones, 1988). Table 2 summarizes the characteristics of chorionic villus and amniotic fluid cultures as defined in this laboratory during the past 12 years.…”
mentioning
confidence: 99%